2016
DOI: 10.1371/journal.pone.0167584
|View full text |Cite
|
Sign up to set email alerts
|

Using Diffusion Tensor Imaging to Evaluate Microstructural Changes and Outcomes after Radiofrequency Rhizotomy of Trigeminal Nerves in Patients with Trigeminal Neuralgia

Abstract: Trigeminal neuralgia is characterized by facial pain that may be sudden, intense, and recurrent. Our aim was to investigate microstructural tissue changes of the trigeminal nerve in patients with trigeminal neuralgia resulting from neurovascular compression by diffusion tensor imaging, and to test the predictive value of diffusion tensor imaging for determining outcomes after radiofrequency rhizotomy. Forty-three patients with trigeminal neuralgia were recruited, and diffusion tensor imaging was performed befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Advancements in imaging methodologies, e.g. diffusion tensor imaging and functional magnetic resonance imaging (fMRI), help us to understand the physiology and pathophysiology of the trigeminal system further (Mainero et al, 2007;Chen et al, 2016;Li et al, 2017). In this article, we aim to provide insights into and a thorough and clear overview of the most noteworthy studies and articles up to today on the neurophysiological sensory aspects of this complex neural system; important anatomic correlations will be reviewed where needed.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in imaging methodologies, e.g. diffusion tensor imaging and functional magnetic resonance imaging (fMRI), help us to understand the physiology and pathophysiology of the trigeminal system further (Mainero et al, 2007;Chen et al, 2016;Li et al, 2017). In this article, we aim to provide insights into and a thorough and clear overview of the most noteworthy studies and articles up to today on the neurophysiological sensory aspects of this complex neural system; important anatomic correlations will be reviewed where needed.…”
Section: Introductionmentioning
confidence: 99%
“…FA describes how much molecular displacements vary in space and is related to the presence of oriented structures [28]. ADC, expressed as square millimeter per second, characterizes the overall mean-squared displacement of molecules and the overall presence of obstacles to diffusion [2, 28].These evidences motivated several studies to examine structural abnormalities in the trigeminal nerve (TGN) of patients with TN using FA [5-7, 9, 10, 13-15, 17, 22-25, 30] and ADC [7,13,17,[23][24][25]. Most of the studies examining FA by comparing the affected and unaffected sides of patients and controls revealed a significant decrease in FA values [5-7, 9, 10, 14, 15, 17, 22-25].…”
mentioning
confidence: 99%
“…Most of the studies examining FA by comparing the affected and unaffected sides of patients and controls revealed a significant decrease in FA values [5-7, 9, 10, 14, 15, 17, 22-25]. Chen et al, Leal et al, and Lummel et al reported a significant elevation in ADC values in the affected sides of patients [7,17,23]. Other three studies did not find differences in ADC values between affected and unaffected sides of patients and controls [13,24,25].…”
mentioning
confidence: 99%
See 2 more Smart Citations